Project Finance: Basic Components - Alfieri Li Ojeda, Jaime (2015)
The natural speed of the contemporary world demands large investment projects which require specialized financial techniques such as Project Finance, defined as a fund to finance investment projects of great magnitude. Every Project Finance involves a wide range of elements such as promoters, government, contractors andsuppliers, among others, that will ensure project success.